Cancun update : trade in services (International Centre for Trade and Sustainable Development GenevaCH, 2003)
Notes the prospects for Cancun. Provides a background to the topic and states the mandated deadlines. Focuses on the current state of play, highlighting the following issues: bilateral market access negotiations; horizontal issues; and subsidiary bodies - outstanding rule-making issues. Identifies implementation issues.
Keywords: TRADE NEGOTIATIONS